The production process of abon nila pak anto in wonogiri central java : a swot analysis - , SUNGGING MANDASIA, Supriyono, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this graduating paper is to know the production process of abon nila and its SWOT analysis (strength, weakness, opportunity, and threat). It situates Pak Anto shop in Wuryantoro, Wonogiri as the object of study. This research focus on production process which Pak Anto has applied and factors that influenced him in choosing nila as the main ingredient. Method of collecting data was done by observation, interview, library research, and internet research. Besides, to analyze the data, this research conducts SWOT analysis method. Pak Anto prefers to choose nila (Oreochromis niloticus) as the main ingredient because it is the better alternative than patin (Pangasius pangasius) and easily find in the area like Waduk Gajah Mungkur. Based on the observation, production process of abon nila is divided into seven steps